Autoantibodies to DNA topoisomerase II in cryptogenic fibrosing alveolitis and connective tissue disease. - Meliconi, R (1989)
Sera from patients with autoimmune lung and connective tissue diseases were investigated for antibodies to topoisomerase II. Anti-topoisomerase II antibodies were detected by ELISA in 37% of sera from patients with cryptogenic fibrosing alveolitis (CFA), in one (8%) case of sarcoidosis and in 31% of sera from systemic lupus erythematosus (SLE) patients. Sera from rheumatoid arthritis, juvenile rheumatoid arthritis, progressive systemic sclerosis, Sjögren's syndrome and undifferentiated connective tissue disease were negative. CFA and sarcoidosis sera strongly reacted in immunoblotting with a 170 kD protein, also recognized by rabbit antiserum to recombinant topoisomerase II, while SLE sera presented a weak reaction. Pre-adsorption with dsDNA dramatically decreased the topoisomerase II binding in ELISA by the most positive SLE serum, but did not affect the binding by the most positive CFA serum, thus indicating that anti-topoisomerase II reactivity of SLE sera is probably due either to cross-reacting antibodies or, in part, to minor DNA contamination of our enzyme preparation. The determination of DNA topoisomerase II relaxation activity, performed after incubation with antibody-positive sera, showed that only CFA sera precipitate enzymatic activity. The finding that CFA presents antibodies to an enzyme essential to cell survival stresses the role of autoimmunity in the pathogenesis of idiopathic pulmonary fibrosis. This may offer further insight into the cause of autoimmune disease and prove a valuable tool in the study of enzyme molecular biology.